Tinjauan Sistematis : Transformasi Pelayanan Metrologi di Era Digital (Metrologi Digital4.0) - Lumbanraja, Penny Chariti; Lumbanraja, Pretty Luci (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2024)
Legal metrology services are very important to answer the need to ensure fairness in trading activities, especially during the weighing and measuring process. Metrology as an important element in trade must also face challenges in adapting to changing times. The application of legal metrology services in trade transaction activities is aimed at protecting every citizen's rights as a whole, whether acting as a business actor or consumer. The rapidly developing transformation is changing society, industry and the economy. Transforming metrology services in the digital era certainly requires a long process. In solving this problem, developing quality digital metrology infrastructure is important. The data analysis technique used in this research is a systematic literature review. From the results of reviews conducted in several studies, it was found that the focus of metrology transformation is on improving the quality of infrastructure for the establishment and development of metrology clouds so as to provide economic benefits and create digital confidence in measurements. The important aim of improving infrastructure quality in digitalization of metrology is to strengthen the three main pillars, namely metrology services, accreditation and standardization.